A educação profissional e o currículo integrado no ensino médio do IFMA: avaliação, percepções e desafios - AGUIAR JUNIOR, Arnaldo Cunha de (2012)
This research investigates two objects in the educational field, which are the Integrated Curriculum and Professional Education, addressing the epistemological principles, historical and legal aspects of these categories. The central focus of analysis is the investigation of the processes involving the Integrated Curriculum and Professional Education in High School at the Federal Institute of Maranhão (IFMA). Searching diagnose whether the deployment of the integrated curriculum in high school technical Federal Institute of Education Science and Technology of Maranhão has contributed to the improvement of human actions within the professionalisation. The main objective is to analyze the Integrated Curriculum in middle school coach, your chances of continuity and / or rupture, construction and social relations in vocational education at the Federal Institute of Education Science and Technology of Maranhao and its contribution to the improvement of pedagogical actions and methodological training adequate to the target audience. Searching further comprise also the history of professional education and integrated curriculum, from theoretical concepts and legal bases; Analyze historically curricular changes in school / vocational technical in the general context and the Federal Institute of Education Science and Technology of Maranhao; Diagnose training faculty with their teaching practices in the disciplines of high school integrated IFMA, and references used in the classroom, and ultimately suggest new ways or suggestions from the assessment conducted on the Integrated Curriculum in IFMA. The study was based on a qualitative approach, through a literature review and studies for the theoretical, assessment, analysis, discussion and assessment of the studied materials, field research using semi-structured technical tools (questionnaires and interviews) with managers, teachers and students, under the theoretical and methodological framework that facilitated information gathering and systematization of knowledge in the process of research and analysis.